PEBEDAAN BOBOT DAN KADAR AIR BENIH KOPI TERHADAP KONSENTRASI HORMON GIBERELLIN (GA3) DAN JENIS AIR - Dede Suhendra; Siska Efendi (UNIVERSITAS LABUHANBATU, 2021)
West Sumatra is one producing coffee area in Indonesia a significant contribution to economy in Indonesian, because production coffee in West Sumatra unstable, it is necessary to expand the area. The propagation plants coffee is carried out in generative manner and needs be optimized with treating gibberellin hormone and water temperature to germination stage of coffee seeds.This research was conducted at the Seed Technology Laboratory of the Faculty of Agriculture, Andalas University from May to August 2021. The parameters observed were initial seed weight (g), seed weight after treatment (g), initial seed moisture content (%), seed moisture content after treatment (%). The results showed that the observation of initial seed weight and initial seed moisture content showed no significant effect. While the data had a significant effect on the observation of seed weight after treatment with the concentration of gibberellin hormone and seed moisture content after treatment in the treatment of water types, where the observation of seed weight after the highest treatment was in the treatment of gibberellin hormone concentration of 400 ppm with aquadest (G4J1) of 4.23 g and on the observation of the water content of the seeds after the highest treatment, namely the treatment with the concentration of the hormone gibberellin 300 ppm with aquadest (G3J1), which is 46.32%. Key words: Seed Weight, Moisture Content, Aquadest